2021
DOI: 10.3390/aerospace8110330
|View full text |Cite
|
Sign up to set email alerts
|

Blade Roughness Effects on Compressor and Engine Performance—A CFD and Thermodynamic Study

Abstract: Degradation of compressors is a common concern for operators of gas turbine engines (GTEs). Surface roughness, due to erosion or fouling, is considered one of the major factors of the degradation phenomenon in compressors that can negatively affect the designed pressure rise, efficiency, and, therefore, the engine aero/thermodynamic performance. The understanding of the aerodynamic implications of varying the blade surface roughness plays a significant role in establishing the magnitude of performance degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Since aerospace technology needs accuracy and high safety standards, before the experiment, several authors simulated the erosion and fouling conditions and their effects on gas turbine engine performance [44][45][46][47][48]. Alqallaf and Teixeira [44] reported degradation of the compressor performance due to eroding environments by linking the compressor aerodynamics with a thermodynamic cycle using Turbomatch, the Cranfield in-house gas turbine performance simulation software. They have uniformly increased blade surface roughness in the first two stages of a low-pressure compressor.…”
Section: Erosion Of Compressor Blades By Sand Particlesmentioning
confidence: 99%
“…Since aerospace technology needs accuracy and high safety standards, before the experiment, several authors simulated the erosion and fouling conditions and their effects on gas turbine engine performance [44][45][46][47][48]. Alqallaf and Teixeira [44] reported degradation of the compressor performance due to eroding environments by linking the compressor aerodynamics with a thermodynamic cycle using Turbomatch, the Cranfield in-house gas turbine performance simulation software. They have uniformly increased blade surface roughness in the first two stages of a low-pressure compressor.…”
Section: Erosion Of Compressor Blades By Sand Particlesmentioning
confidence: 99%
“…Such a process permits a substantial level of flexibility when investigating alternative operational arrangements for GTEs. A comprehensive explanation of the Turbomatch tool is presented in [5]. A schematic representation of the complete research engine model is shown in Figure 1.…”
Section: Turbomatch Performance Toolmentioning
confidence: 99%
“…The LPC comprises inlet guide vanes (IGV), second rotor (R2), second stator (S2), third rotor (R3) and third stator (S3), comprising a total of 458 blades. Comprehensive technical details of the research engine can be found in [5]. For the geometric details of the research engine showing the locations of the IGV and first two stages of the LPC, see Figure 2.…”
Section: Case Study Detailsmentioning
confidence: 99%
See 2 more Smart Citations